EVALUATING THE EFFICACY OF ALUMINUM PHOSPHATE FORMULATED L2 BASED HUMAN PAPILLOMA VIRUS VACCINE - RAJANATHAN TM, CHOZHAVEL; G, LAKSHMIKANTH; P, AGASTIAN (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Human papilloma virus (HPV) caused cervical cancer the second most common cancer among women worldwide and the most common cancer in developing countries like India. Though, currently type specific prophylactic vaccine have been developed, there is a need for cross protective virus neutralizing vaccine. In this study we have tried to show the multi-epitope vaccine and check the final Alum adjuvant formulated vaccine antibody titer. Methods: Our study was targeted to analyses the in vivo vaccine efficacy of the aluminum adjuvant formulated recombinant multi epitope antigen with two different grades of aluminum phosphate (pH 5.5 & 6.4). Neutralizing antibody titters against the major neutralizing epitope 17-36 aa region of the N-terminal domain. Results: The results of this study showed that the final aluminium adjuvant recombinant L2 based multi-epitope vaccine produced antibody against 17-36 peptide one of the proven major virus neutralizing epitope. Conclusion: L2 based multi-epitope recombinant antigen formulated with aluminium adjuvant can be an low cost, broadly protective HPV vaccine. Keywords: Human papilloma virus L2, Multi-epitope recombinant vaccine, Aluminum adjuvant. Â